Menace of Middlemanship in the Light of Islamic Teachings - Khalid Mahmood Lodhi; Ahmed, Naeem (Islamic Banking and Finance Review, 2021)
Despite abundant agricultural production, the prices of fruits, vegetables, and other agricultural items remain high, keeping these products out of the a common man’s reach. Although small and poor farmers work hard throughout the year, yet they remain indebted and poor. There might be various reasons for their plight such as the extraordinarily high prices of agri-food items; however, the role of the middleman (Arhti) seems to be the most damaging in this regard. This paper analyses the role palyed by the middleman in Pakistan in the light of Islamic teachings and primary (through survey questionnaire) and secondary data. The study found that generally, the middleman is a cruel character and causes distortions in the economy, particularly in the agro-food market. He deprives poor farmers of meaningful profit, keeps them under the pressure of debt, and causes price hikes of essential items which leads to artificial inflationary pressures in the economy. Ultimately, this phenomenon exerts pressure on the government as well. The current study also found that the presence of middleman in the supply chain of agro-food items deprives poor farmers of their right of earning genuine profit.Moreover, it also increases the price of essential food items. Hence, in the light of Shariah guidelines, unnecessary brokering needs to be restricted so that farmers are able to sell their produce themselves. Furthermore, the middleman’s role needs to be curtailed for the welfare of the farmers, improvement of the agriculture sector, and the betterment of the economy. The study recommends the framing of comprehensive long-term policies for the purchase of crops, monitoring of fruit / vegetable markets, provision of interest-free loans to farmers, setting up of an efficient market mechanism, establishment of effective consumer courts, and the improvement of the transportation system.